Child Migration and Human Rights in a Global Age - Jacqueline Bhabha (Princeton University Press, 2014)
Every year, tens of thousands of children cross borders alone. Some travel to join families that have already migrated. Others leave home to flee war, civil unrest, natural disaster, or persecution. Some migrate in search of work, education, opportunity, adventure. Others travel separated from their families but not actually alone, in the company of traffickers or smugglers, risking exploitation and abuse. The majority, perhaps, travel for a combination of reasons, part of the growing trend toward mixed migration. And yet, the complexity of child migration is a largely untold and unanalyzed story. This book is an effort to correct that omission. Child migration is part of a contemporary phenomenon that changes and shapes the world we live in. Migration affects not just the 3 percent1 of the global population who are migrants, but the vast majority who are not. As villages become depleted of young adults and the population in metropolitan centers changes beyond recognition within the space of a couple of decades, as schools, hospitals, workplaces, and shops cater to an increasingly diverse clientÃ¨le, so the cumulative impact of contemporary migration irrevocably seeps into the fabric of everyday life. Many stories have been told about this process, ranging from alarmist xenophobic accounts of invasion and cultural pollution to cautious academic analyses of the impact of migration flows on population stocks and domestic economic prospects. They are interspersed with a range of literary and cinematic depictions of the imaginative correlates of migration. Very few of these stories center on the experiences of child migrants, the push and pull factors affecting their movements, and the social and legal environments they populate. This deficit is nontrivial. It affects the perception of migration as a whole and the social investment it attracts. Migration is increasingly considered a voluntary adult phenomenon requiring management and control. The claim to protective intervention or fiscally backed social engagement is ever-diminishing now that concerns about the Holocaust and the brutalities of the Cold War have given way to apprehensions about terrorists and welfare scroungers. Children do not feature in this large-scale picture, except as occasional appendages to adults. But they should. The failure to attend to child migration coincides with the diffusion of confused, unsatisfactory, and frequently oppressive policies that should not stand up to careful public scrutiny.